Banking service quality management using fuzzy FMEA (a case study: Central Melli Bank of Rafsanjan). (2016) - Mirghafori, Seyed Habibolah; Takalo, Salim Karimi; Dastranj, Meysam
The purpose of all service institutions, including banks, is to provide appropriate services for the customers' satisfaction. Therefore, due to the importance of quality in service industries and its significant effects on customer satisfaction, the question arises: how the quality of service can be evaluated? This case study also sought to assess the quality of banking services using failure mode and effect analysis (FMEA) techniques in fuzzy environment in one of the branches of Melli Bank of Rafsanjan. In FMEA technique, the risk priority number (RPN) index was used for rating the failure items, which is the multiplication of three risk factors: occurrence of failure, severity of failure and detectability of failure. In FMEA technique, the weights of risk factors weight are not taken into account, such that, the same weight value is assumed for each of those factors. To overcome this weakness, much research has been performed, recently. This paper uses Wang and colleagues' model in a fuzzy environment. The results illustrate that one of the most significant failure items is lack of a proper location to park the customers' car.